Is John’s Gospel antisemitic? With special reference to its use of the Old Testament - Balfour, Glenn (1995)
We begin by observing the growing awareness among New Testament scholars of the key issues: the ‘elasticity’ of first century Jewish faith, sufficient to encompass many Jewish Christian groups; and the necessity for a correct terminology which not least distinguishes religious from racial polemic. We also observe the state of relations between Jews and ‘outsiders’ leading up to the first century CE, to discover that, excepting the Alexandrian situation, they were generally good. We then examine John’s use of the Old Testament, first in his citations, then in his allusions. It becomes clear that John not only makes extensive use of the Jewish scriptures, but that those scriptures are essential to every facet of his Gospel. Since he also makes extensive use of contemporary Jewish exegeses of the Old Testament we conclude that he must hail from a Jewish (Ephesian) community, an identity he positively promotes in his presentation of Jesus Messiah. Since he often does not explain his use of the Old Testament, without which his message is lost, we further conclude that his readers too are Jewish. Finally, since his message has a specifically evangelistic as well as confirmatory component, we conclude that John’s purpose is to bolster his community’s faith and, via its members, to convince still wavering members of the synagogue the community has been expelled from, that Jesus is Messiah. This necessitates a reassessment of John’s polemic against οἱ Ἰουδαῖοι: it refers to all Jews who reject the Messiah (as opposed to us Jews who accept him). John’s replacement christology too must be seen as part of the internal Jewish response to the Temple destruction: he offers Jesus as the restoration of the lost cultus, just as the Yavnean inheritors of the Pharisaic legacy offer halakah. We end by noting that the only effective means of ensuring a non-antisemitic interpretation of John’s Gospel among its modern readers, both Jews and Christians, is to return the Gospel to this Jewish setting.